Green waqf implementation strategy as an acceleration of green project funding: A case study of Rongkop Gunungkidul special region of Yogyakarta - Marlita Wulansari; Rahmawati, Anisa (Universitas Negeri Yogyakarta, 2025)
Rongkop is a karst area that is prone to drought and difficult to access water. This causes a negative multiplier effect to various aspects, such as social, economic, and ecological. Several efforts have been planned but are constrained by the availability of funds. Therefore, there is a green waqf that focuses on financing environmentally friendly projects. The purpose of this study is to analyze the implementation strategy of green waqf as an acceleration of environmentally friendly project funding by modifying the futuristic stages in the Green Waqf Framework book compiled by BWI and other institutions. This study uses a descriptive qualitative approach with data collection techniques through interviews, observations, and literature studies. The data analysis procedure adopts the Miles and Huberman model which starts from collection, reduction, presentation, data as well as conclusion and verification. The findings of the study revealed that Rongkop has a population with most Muslims, but almost the entire community does not know about green waqf. Therefore, the stages are designed starting from the preconditional stage to build awareness of green waqf. Consolidation stage to strengthen the elements and stakeholders involved. Next, the project development stage is through pilot projects and periodic impact measurements. Also, mainstreaming the stage by disseminating the results of the pilot project to various regions and institutions. With the implementation of green waqf, it is hoped that environmental issues and climate change in various regions can be addressed inclusively.